SAT0501 Early versus late-onset systemic sclerosis: are there clinical and immunological differences?. (12th June 2018) - Luís, M.; Costa, F.; Carmo, A.; Ferreira, J.; Santiago, T.; Cunha, R.; Salvador, M.J.; da Silva, J.
Abstract : Background: The clinical course of Systemic Sclerosis (SSc) depends on subtype, organ involvement and age. Peak age at onset of SSc is between 30 and 50 years, although SSc may also start in both young and elderly patients. Few data have been reported on patients suffering from late-onset SSc. Objectives: To characterise clinical and immunological features of early and late-onset SSc in a tertiary referral hospital. Methods: We analysed data from 178 patients followed at our SSc clinic. All the patients fulfilled the ACR/ EULAR 2013 classification criteria for SSc or the LeRoy's criteria for the classification of early SSc. Based on the mean of age of onset of the whole series (50±15 years), ages extremes were defined as younger than 35 versus older than 65 years of age at onset. Disease characteristics as well as clinical and immunological features were evaluated. Results: The early and the late-onset groups included 35 and 31 patients, respectively. Patients' current mean age was 42.8±14.1 vs. 75.8±6.2 with a mean disease duration of 14.5±14.7 vs. 4.3±4.6 years. The most common first manifestation of disease was Raynaud phenomena followed by arthritis/inflammatory arthralgia, in both groups. However, the time between clinical onset and SSc diagnosis was higher in the late-onset group (p=0.034). A higher number of diffuse and pre-SS was observed in the early group but this difference didn't prove statistically significant. There was a higher prevalence of centromere antibodies in the late-onset group (p=0.001). Clinical manifestations and target-organ damage didn't differ between groups, except for a higher prevalence of heart conduction abnormalities in the late-onset group (p=0.02). In multivariate analyses, age alone (OR=1.04; 95% CI 1.0, 1.1), but not disease duration (OR=0.99; 95% CI 0.9–1.0), was an independent predictor for the presence of heart conduction abnormalities. Conclusions: In line with findings from other studies, late-onset SSc shows a distinct clinical and immunological presentation. The present study confirms that late-onset is associated with longer diagnostic delay, positive centromere and heart conduction abnormalities. These observations may be due to age and potential age-associated confounders, rather than the disease itself. Knowledge of these different characteristics can help to improve the management of the disease. References: [1] Alba M, et al. Early-versus Late-Onset Systemic Sclerosis. Medicine2014;93(2):73–81. [2] Hugle T, et al. Late-onset systemic sclerosis – a systemic survey of the EULAR scleroderma trials and research group database. Rheumatology (Oxford)2010;50(1):161–5. [3] Manno R, et al. Late-Age Onset Scleroderma. J. Rheumatol2011;38(7):1317–1325. Disclosure of Interest: None declared